INTENTION TO INFAQ AND SEDEKAH VIA DIGITAL PLATFORMS: THE CASE OF MUSLIM STUDENTS IN JAVA - Mahmudza, Gita Ami; Sudarsono, Heri (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
The research analyzes the factors influencing students' intentions toward infaq and sedekah through digital platforms. This research involved 226 respondents from Java who had carried out transactions using digital platforms. Respondents were selected randomly using a simple random sampling technique, and data was collected through a questionnaire with a Likert scale. The analytical method used in this research is partial least squares, consisting of outer and inner models. Hypothesis testing checks the original sample, T-statistics, and P-value on the bootstrap results. The research results show that performance expectancy and social influence behavior intention while facilitating conditions and behavioral intention influence use behavior. However, no influence was found on behavior intention between effort expectancy and reducing conditions.